Students' Perspectives on Teaching Materials for English Reading Comprehension - Ginting, Yun Fiber Almanda; Liana, Friscilla Sembiring; Liana; Prayuda, Meikardo Samuel (Jurnal Pendidikan dan Pengajaran, 2025)
One of the common problems in teaching English Reading Comprehension at the college level is the mismatch between the teaching materials and the student’s proficiency level. This study explores students’ perceptions of the effectiveness of the teaching materials used in the English Reading Comprehension course and how they affect their learning experience. This study used a mixed methods approach, combining quantitative and qualitative methods. The subjects of the study consisted of 60 second-semester students of the English Language Education Study Program, who were selected through a total sampling technique from three different classes taught by lecturers A, B, and C. Data were collected through a Likert-scale questionnaire to assess clarity, relevance, use of multimedia, and motivational impact, and semi-structured interviews to dig deeper into the information. Quantitative data analysis was conducted descriptively, while qualitative data were analyzed using a thematic approach. The results showed that the materials from Lecturers A and B received positive assessments, while those from Lecturer C were less effective. The conclusion of this study confirms that structured, proficiency-appropriate, and multimodal teaching materials can significantly improve students’ comprehension and engagement. The implications of these findings highlight the importance of student-centered and innovative teaching approaches in higher education curriculum development.